The Influence of High Performance Work Practices (HPWP) on Intention to Leave among Ahass Mechanics in Purbalingga Regency - Dwita Setiyani; Najmudin, Najmudin; Sudarto, Sudarto (International Journal of Education, Vocational and Social Science, 2024)
In service provider businesses, human resources are the key differentiator and add value which becomes a competitive advantage. The aim of this research is to analyze the effect of ability enhancing HPWPs on intention to leave, secondly motivation enhancing HPWPs based on evaluation of intention to leave, thirdly motivation enhancing HPWPs based on security on intention to leave, and fourth opportunity enhancing HPWPs based on security on intention to leave. The method used in this research is a quantitative approach with 100 AHASS mechanics as respondents and analysis using multiple linear regression. The results of this research are that ability enhancing HPWPs has a positive and significant effect on intention to leave, secondly motivation enhancing HPWPs based on evaluation has a positive and significant effect on intention to leave, thirdly motivation enhancing HPWPs based on security has a positive and significant effect on intention to leave, and fourthly opportunity enhancing HPWPs based on security have a positive and significant effect on intention to leave.